2021
DOI: 10.1007/s12350-020-02140-1
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest repeatability and software reproducibility of myocardial flow measurements using rest/adenosine stress Rubidium-82 PET/CT with and without motion correction in healthy young volunteers

Abstract: Background. Myocardial flow reserve (MFR) assessment with cardiac positron emission computed tomography (PET/CT) is well established, and quantification relies on commercial software packages. However, for reliable use, repeatability and reproducibility are important. The aim of this study was therefore to investigate and compare between scans and software packages the repeatability and reproducibility of 82 Rb-PET/CT estimated MFR.Methods and Results. Forty healthy volunteers completed two 82 Rb-PET/CT rest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…The study did not consider motion correction, which could affect the accuracy of kinetic quantification [45][46][47][48]. Nevertheless, the effect of motion is not expected to result in a significant change to the results of this study since the spatial resolution of the PET scanner is only about 6-8 mm and the quantification was performed on large, global ROIs.…”
Section: Discussionmentioning
confidence: 90%
“…The study did not consider motion correction, which could affect the accuracy of kinetic quantification [45][46][47][48]. Nevertheless, the effect of motion is not expected to result in a significant change to the results of this study since the spatial resolution of the PET scanner is only about 6-8 mm and the quantification was performed on large, global ROIs.…”
Section: Discussionmentioning
confidence: 90%
“…Internal reproducibility of the CFVR results were good and therefore not the cause of the modest agreement between methods, while PET examinations were not repeated. Interestingly, other studies of MBFR measurement found only modest agreement between repeated PET examinations (107,108). Overall, it was concluded that CFVR and MBFR in ANOCA patients are not interchangeable, possibly due to the methodological differences.…”
Section: Other Modalitiesmentioning
confidence: 85%
“…All PET acquisitions, targeting injection doses of 1100 MBq 82 Rb supplied from a CardioGen‐82 Sr‐82/Rb‐82 generator (Bracco Diagnostics Inc.), were obtained in three‐dimensional mode on a 128‐slice Biograph mCT PET/CT system (Siemens Healthineers) and stored in list‐mode format (Murthy et al, 2018 ). Pharmacologic stressing was obtained using adenosine infused at 140 mcg/kg/min for 6 min with PET emission acquisition starting 2.5 min into the infusion, Before the rest scans, the patients underwent a low‐dose CT for attenuation–correction purposes (120 kVp; effective tube current, 26 mA [11 mAs quality reference]) acquired using a free‐breathing protocol (Byrne et al, 2021 ). Coronary artery calcium score (CACS) images were acquired from a noncontrast breath‐hold CT scan and CACS was calculated according to the Agatston score (Agatston et al, 1990 ).…”
Section: Methodsmentioning
confidence: 99%